The Role of Lawyer-Legislators in Shaping the Law: Evidence from Voting Behavior on Tort Reforms - Ulrich Matter; Alois Stutzer (Institute for the Study of Labor (IZA), 2015)
Attorneys elected to the US Congress and to US state legislatures are systematically less likely to vote in favor of tort reforms that restrict tort litigation, but more likely to support bills that extend tort law than legislators with a different professional background. This finding is based on the analysis of 64 roll call votes at the federal and state level between 1995 and 2014. It holds when controlling for legislators' ideology and is particularly strong for term-limited lawyer-legislators. The empirical regularity is consistent with the hypothesis that lawyer-legislators, at least in part, pursue their private interests when voting on tort issues. Our results highlight the relevance of legislators' identities and individual professional interests for economic policy making.
Keywords: D72; K13; 330; lawyers; legislatures; rent-seeking; tort law; tort reform; voting behavior